Comparison between two insecticide application methods in controlling lesser mealworm beetles in commercial broiler housessser mealworm beetles in commercial broiler houses (Revista de Ciências Agroveterinárias, 2019)
The lesser mealworm control is mostly made by insecticides, as the association of chlorpyrifos, cypermethrin and citronellal. The traditional insecticide application method (TRADM) depends on many liters of water and, with the objective of reducing water consumption, the aim was to compare TRADM with atomizer-equipment method (ATOMM). Four and three houses from farm A and B were used, respectively. Houses 1, 3 and 7 were treated with TRADM (1 liter of insecticide diluted in 500 liters of water) and houses 2, 4, 5 and 6 with ATOMM (1 liter of insecticide diluted in 9 liters of water). Twenty-four hours before and 30 (for farm A) and 45 days (for farm B) after the insecticide application, the number of insects was counted in each house (using 18 mapped traps/house). Farms were not considered different (p>0.05) and comparison was made between the houses. Houses were different (p
Keywords: Alphitobius diaperinus; atomizer; insect control; poultry